1:1 internal mode coupling strength in GaAs doubly-clamped MEMS beam resonators with linear and nonlinear oscillations. (17th December 2020) - Zhang, Ya; Yoshioka, Yuri; Morohashi, Isao; Liu, Xin
Abstract: We have investigated the 1:1 internal mode coupling strength in a GaAs doubly-clamped MEMS beam resonator by thermally tuning the frequencies of two neighbored resonant modes. The anti-crossing of the resonant frequencies indicates that the two modes couple with each other, and the mode coupling strength was estimated by the splitting of the anti-crossed frequencies of the two modes. When the oscillation amplitudes were tuned from the weakly-driven linear regime to the strongly-driven nonlinear regime, we observed slightly increased frequency splitting, indicating that the nonlinear oscillation only makes a very small contribution to the mode coupling strength.